Influence of parameters on the ultimate penetration depth of a double-plate vertically loaded anchor in soft clay - Xing, Guoqi; Cao, Yupeng; Zhang, Baoliang; Li, Jian; Zhang, Xiaotong (Frontiers in Materials, 2023)
To make a new type of double-plate vertically loaded anchor (DPVLA) penetrate into clay deeper, the influence of parameters on the ultimate penetration depth of DPVLAs in soft clay should be investigated. The expression of ultimate penetration depth applicable to DPVLAs in clay was determined in terms of the formula of ultimate penetration depth of anchors with a wedge-shaped section. Based on the drag penetration tests, the movement direction of the bottom fluke of DPVLAs with different lengths of bottom fluke and different included angles was obtained. By the finite element method, the upper bound solutions of bearing capacity factors of DPVLAs with different included angles and different lengths of bottom flukes were also obtained, which correspond to the maximum penetration depth induced by the initial orientation of the anchor. According to the determined expression of the ultimate penetration depth of DPVLAs, the ultimate penetration depth of DPVLAs with different included angles and different lengths of the bottom fluke in clay can be calculated. The results showed that increasing the length of bottom fluke can increase the ultimate penetration depth when the included angles were the same for DPVLAs not only in the clay with zero strength at the seabed but also in the clay with uniform strength. However, when the length of the bottom fluke was the same, increasing the included angle of DPVLAs in clay can significantly reduce the ultimate penetration depth.